Parametric Optimization of Friction Torque and Bearing Temperature in Tapered Roller Bearings Using Response Surface Methodology - Amisha B. Khant; Jaydeep K. Dadhaniya; Hardik G. Chothani (ITEGAM-JETIA)
Friction torque at high axial load increase rapidly which also raise the bearing temperature in tapered roller bearings (TRBs) that leads to major power loss and heat generation within bearing and ultimately lower bearing performance. In TRBs, at high axial load, inner raceway rib convexity plays an important role by providing resistance to friction and support the bearing. In present study, parametric optimization of friction torque and bearing temperature of TRBs are carried out using Response Surface Methodology (RSM). The RSM Box-Behnken design was used to design experiments and regression model is developed to establish the relation between input parameters inner race rib convexity, axial load and bearing shaft speed accurately. The minimum friction torque and bearing temperature are achieved at 7.96 Nm and 54.57 °C respectively at rib convexity 3.21 µ, axial load 2000 kgf and 400 bearing shaft rpm.